When the Heat Is On: The Effect of Temperature on Voter Behavior in Presidential Elections - Van Assche, Jasper; Van Hiel, Alain; Stadeus, Jonas; Bushman, Brad J.; De Cremer, David; Roets, Arne (Frontiers in Psychology, 2017)
Hot temperatures lead to heightened arousal. According to excitation transfer theory, arousal can increase both antisocial and prosocial behavior, depending on the context. Although many studies have shown that hot temperatures can increase antisocial behavior, very few studies have investigated the relationship between temperature and prosocial behavior. One important prosocial behavior is voting. We analyzed state-level data from the U.S. presidential elections (N = 761). Consistent with excitation transfer theory, which proposes that heat-induced arousal can transfer to other activities and strengthen those activities, changes in temperature and voter turnout were positively related. Moreover, a positive change in temperature was related to a positive change in votes for the incumbent party. These findings add to the literature on the importance of non-ideological and non-rational factors that influence voting behavior.